Re-Imagining Healthcare and Medical Research Systems in Post-Devolution Scotland. (March 2019) - Mittra, James; Mastroeni, Michele; Haddow, Gill; Wield, David; Barlow, Elisabeth
We use the concept of 'imagined communities', and related work on socio-technical imaginaries and expectations, to reflect on how Scotland is represented simultaneously as 'sick and unhealthy' and a 'living lab' due to its innovative medical research. Together, we suggest these narratives have driven a broader health and wealth agenda in post-devolution Scotland, which became salient during the 2014 independence referendum. We draw on research conducted during the independence referendum to consider how key stakeholders enacted imagined communities/identities (sick but also innovative) as they considered the historical impact of devolution on health and research systems and envisioned future independence. The referendum provided an opportunity to consider how Scottish health and research systems have been imagined over time. Our findings further the understanding of the impact of devolution on healthcare and medical research, revealing the role played by policy narratives rooted in imagined identities.